2016
DOI: 10.1016/j.ijinfomgt.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

A resiliency framework for an enterprise cloud

Abstract: Abstract-This paper presents a systematic approach to develop a resilient software system which can be developed as emerging services and analytics for resiliency. While using the resiliency as a good example for enterprise cloud security, all resilient characteristics should be blended together to produce greater impacts. A framework, Cloud Computing Adoption Framework (CCAF), is presented in details. CCAF has four major types of emerging services and each one has been explained in details with regard to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…An organisation that implemented I4.0 is expected to have a system that is adaptive by plugand-work mechanism (Monostori et al, 2016), autonomous (Letia & Kilyen, 2018), decentralised (Terziyan et al, 2018), dependable (Alguliyev et al, 2018), interoperable (Priyadarshinee et al, 2017), capable of real-time operations (Terziyan et al, 2018), remote monitoring and control (Sung, 2018), resilient (Chang et al, 2016), robust (Alguliyev et al, 2018), capable of handling full information (Sabherwal & King, 1991), flexible (Browne et al, 1984), capable of maintaining data lifecycle (Tao et al, 2018), usable (Priyadarshinee et al, 2017), and with intelligent lots (Li et al, 2012). Given that such capabilities are made possible by critical I4.0 technologies, an organisation is more likely to confirm the continued adoption of such technology, based on trials when its performance meets prior expectations.…”
Section: Post-adoption Stagementioning
confidence: 99%
“…An organisation that implemented I4.0 is expected to have a system that is adaptive by plugand-work mechanism (Monostori et al, 2016), autonomous (Letia & Kilyen, 2018), decentralised (Terziyan et al, 2018), dependable (Alguliyev et al, 2018), interoperable (Priyadarshinee et al, 2017), capable of real-time operations (Terziyan et al, 2018), remote monitoring and control (Sung, 2018), resilient (Chang et al, 2016), robust (Alguliyev et al, 2018), capable of handling full information (Sabherwal & King, 1991), flexible (Browne et al, 1984), capable of maintaining data lifecycle (Tao et al, 2018), usable (Priyadarshinee et al, 2017), and with intelligent lots (Li et al, 2012). Given that such capabilities are made possible by critical I4.0 technologies, an organisation is more likely to confirm the continued adoption of such technology, based on trials when its performance meets prior expectations.…”
Section: Post-adoption Stagementioning
confidence: 99%
“…Existing process descriptions of APTs (Tankard 2011;Dorey and Leite 2011;Smith 2013;Sood and Enbody 2013;Brewer 2014;Kim et. al 2014;Moon et al 2014;Steer 2014;Virvilis et al 2014;Maisey 2014;Wangen 2015;and Chang et al 2016), are presented 'as-is' without any theoretical basis, comprehensive explanation or description of their development from first principles. Moreover, process descriptions (see Brewer (2014), Moon et al (2014), Virvilis et al (2014), and Wangen (2015) only adequately describe APT missions aimed at obtaining information.…”
Section: Apts: Origin and Evolution Of The Conceptmentioning
confidence: 99%
“…Also in smart cities, information on individuals is open to analysis and sharing which gives rise to concerns about profiling, stealing and loss of control (Hashem & Targio et al, 2016). To address these concerns researchers in (Bello-Orgaz et al, 2016;Chang, Ramachandran, Yao, Kuo, & Li, 2016) have identified different privacy issues that require further research in the future such as data communication, graph matching, awareness, and evaluation of privacy-preserving services.…”
Section: Conclusion and Implications For Researchers And Practitionersmentioning
confidence: 99%